Antileukemic activity and cellular effects of the antimalarial agent artesunate in acute myeloid leukemia. (August 2017) - Kumar, Bijender; Kalvala, Arjun; Chu, Su; Rosen, Steven; Forman, Stephen J.; Marcucci, Guido; Chen, Ching-Cheng; Pullarkat, Vinod
Highlights: Artesunate has potent antileukemic activity against AML in vitro and in murine models of AML. The cytotoxicity of artesunate against AML is mediated by induction of reactive oxygen species. Artesunate augments cytotoxicity of chemotherapy as well as the BCL-2 inhibitor venetoclax in AML. Abstract: The artimisinins are a class of antimalarial compounds whose antiparasitic activity is mediated by induction of reactive oxygen species (ROS). Herein, we report that among the artimisinins, artesunate (ARTS), an orally bioavailable compound has the most potent antileukemic activity in AML models and primary patients' blasts. ARTS was most cytotoxic to the FLT3-ITD+ AML MV4-11 and MOLM-13 cells (IC50 values of 1.1 and 0.82 μM respectively), inhibited colony formation in primary AML and MDS cells and augmented cytotoxicity of chemotherapeutics. ARTS lowered cellular BCL-2 level via ROS induction and increased the cytotoxicity of the BCL-2 inhibitor venetoclax (ABT-199). ARTS treatment led to cellular and mitochondrial ROS accumulation, double stranded DNA damage, loss of mitochondrial membrane potential and induction of the intrinsic mitochondrial apoptotic cascade in AML cell lines. The antileukemic activity of ARTS was further confirmed in MV4-11 and FLT3-ITD+ primary AML cell xenografts as well as MLL-AF9 syngeneic murine AML model where ARTS treatment resulted in significant survival prolongation of treated mice compared to control. Our results demonstrate the potent preclinical antileukemic activity of ARTS as well as its potential for a rapid transition to a clinical trial either alone or in combination with conventional chemotherapy or BCL-2 inhibitor, for treatment of AML.